Emergent Awake tracheostomy—The five‐year experience at an urban tertiary care center. (24th June 2015) - Fang, Christina H.; Friedman, Remy; White, Priscilla E.; Mady, Leila J.; Kalyoussef, Evelyne
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis There are few studies that discuss the issues surrounding emergent awake tracheostomy. We aim to review the indications, anesthesia used, complications, and outcomes of patients undergoing urgent awake tracheostomy. Study Design Chart review. Methods Medical charts of patients who underwent an emergent awake tracheostomy at our institution‐affiliated tertiary care center over a 5‐year period from 2009 to 2014 were reviewed. Data were collected from inpatient, outpatient, and operative records. Results Sixty‐eight patients underwent emergent awake tracheostomy. Over half presented with hoarseness (n = 37, 54.4%) and/or stridor (n = 37, 54.4%). Acute upper airway obstruction secondary to malignancy was the most common indication and accounted for 58 cases (85.3%). Thirty‐nine (70.1%) of the 55 patients with squamous cell carcinoma presented with advanced disease (stage III or IV). Other indications included glottic or subglottic stenosis (4.4%), failure to intubate (2.9%), and other (7.4%). Local anesthesia was used alone in 35.3% of cases and in combination with conscious sedation in 64.7% of cases. Mild bleeding occurred postoperatively in five patients (7.4%). There were no other postoperative complications. Nineteen patients were lost to follow‐up. The mean follow‐up of 49 patients was 7.2 weeks, ranging from 2 to 261 weeks. Long‐term complications occurred in three patients and included tracheitis 7.4% and suprastomal granuloma 2.9%. Eleven patients (22%) were decannulated at a mean of 11.8 months following tracheostomy. Conclusions Emergent awake tracheostomy should be considered in patients with impeding airway obstruction and is a safe and effective method to secure an airway in these patients. Level of Evidence 4 Laryngoscope, 125:2476–2479, 2015